'A Dark Stone in My Stomach': Interventions for Survivors of Mass Violence and Building Sustainable Peace. Issue 3 (December 2016) - Gitau, Lydia Wanja; Rhodes, Paul
The nature and form of interventions received by survivors of mass violence in conflict situations both directly and indirectly impact on the survivors' ability to support building sustainable peace and development. This article examines the role of sensitivity to the trauma experienced by the survivors in the interventions provided after mass violence. By examining the experiences and perceptions of South Sudanese refugees in Kakuma Refugee Camp in Northwestern Kenya, this article explores the complex interplay of violence, trauma, interventions, peacebuilding and development. Interventions that take into consideration the multifaceted ways in which the survivors experience and respond to traumatic events, encourage capacities for resilience in the survivors, engage the creative arts, and emphasise the centrality of community and relationships, may assist the survivors in recovery from trauma and facilitate sustainable peacebuilding and development, as well as avert the possibility of recurring violence.